Metal Free Sequential [3+2]-Dipolar Cycloadditions using Cyclooctynes and 1,3-Dipoles of Different Reactivity - Sanders, Brian C. (2010)
Although metal free cycloadditions of cyclooctynes and azides to give stable 1,2,3-triazoles have found wide utility in chemical biology and material sciences, there is an urgent need for faster and more versatile bioorthogonal reactions. We have found that nitrile oxides and diazocarbonyl derivatives undergo facile 1,3-dipolar cycloadditions with cyclooctynes. Cycloadditions with diazocarbonyl derivatives exhibited similar kinetics compared to azides whereas the reaction rates of cycloadditions with nitrile oxides were much faster. Nitrile oxides could conveniently be prepared by direct oxidation of the corresponding oximes with BAIB and these conditions made it possible to perform oxime formation, oxidation and cycloaddition as a one-pot procedure. The methodology was employed to functionalize the anomeric center of carbohydrates with various tags. Furthermore, oximes and azides provide an orthogonal pair of functional groups for sequential metal free click reactions and this feature makes it possible to multi-functionalize biomolecules and materials by a simple synthetic procedure that does not require toxic metal catalysts.